The Mind of Mr. Soames Based on a Novel by Charles Eric Maine - Maine, Charles Eric (INDICATOR, 2018)
Based on a best-selling novel by Charles Eric Maine, Amicus Productions' "The Mind of Mr. Soames" is a contemporary reworking of the Frankenstein story. Terence Stamp is a young man left comatose from birth, who is awakened live on TV into a world he can't comprehend, and exploited as a living curiosity. Remarkably prescient in its depiction of reality television and media turpitude, the film also boasts a superb supporting cast, including Robert Vaughn, Nigel Davenport, Christian Roberts, Donal Donnelly and Vickery Turner, and features luminous cinematography by the great Billy Williams. [www.powerhousefilms.co.uk]